Accuracy of transverse cerebellar diameter measurement by ultrasonography in the evaluation of foetal age - L., Ravindernath M.; Reddy, Mahender; Reddy, Nihar (International Journal of Advances in Medicine, 2017)
Background: Assessment of accurate gestational age of fetus is very imperative for proper obstetric management of normal as well as IUGR pregnancies. The objective of this study was to evaluate the accuracy of transverse cerebellar diameter as against the conventional parameters of Biparietal diameter, head circumference, abdominal circumference and femur length in normal pregnant mothers between 15 to 40 weeks and in antenatal diagnosis of intrauterine growth retardation. Methods: Study done on 100 women attending antenatal department, 80 were normal pregnancy cases and 20 were clinically suspected IUGR cases. In each patient BPD, HC, AC, FL and TCD was measured. Correlation of TCD was done with other measured parameters as well as with estimated gestational age of fetus. Results: There was no statistically significant difference between the age and parity distributions of two groups It was seen that 18 cases were below the fifth percentile for AC and HC, 19 cases were below the fifth percentile for BPD and 16 cases were below the fifth percentile for FL. In 16 out of 20 cases the TCD values were within the normal range. Only in 4 cases the TCD values were below the 5th percentile. This difference in number of cases below the 5th percentile for BPD, HC, AC, FL and TCD was statistically significant (p-value=0.001). In 20 IUGR cases the gestational age predicted by transverse cerebellar diameter measurements closely correlated with gestational age predicted by last menstrual period. Conclusions: It was found that there is good correlation between TCD and other parameters. Also, TCD shows good correlation with gestational age. It is better than BPD in circumstances like excessive moulding and dolichocephaly. Also, TCD measurement is not fraught with problems as encountered in FL measurement.